Seismic Vulnerability Assessment of an Infilled Reinforced Concrete Frame Structure Designed for Gravity Loads. Issue 2 (17th February 2017) - Pavese, Alberto; Lanese, Igor; Nascimbene, Roberto
Abstract : In the last decades, particular attention has been paid to the seismic vulnerability of existing reinforced concrete buildings designed for gravity loads only. Such buildings, designed before the introduction of capacity design in modern seismic codes, are very common, particularly in seismic prone countries of the Mediterranean area. Due to poor detailing and lacking of capacity design principles, high vulnerability has been highlighted in several past studies. In this article, inadequate seismic response and peculiar damage pattern are investigated by means of shake table tests performed on a 1:2 scaled 3-story infilled prototype. Particular attention is given to the role of beam-column joints and frame-panel interaction. The effectiveness of the EC8-based assessment approach is then evaluated; both linear and nonlinear numerical models, with different levels of sophistication, have been implemented in order to explore their behavioral aspects.